Strategi Bertahan Hidup Pedagang Kaki Lima (PKL) - Muhammad Hayat (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
Indonesian development policy which tends to focus on the growth model has implied on the high concentration of city development. Cities, in fact, fially become spaces where city dwellers and city new comers tightly complete each other to grab the available capital. The qualifid new comers who possess good competence are able to survive in the city. Those people will be able to enjoy the delicious economic cakes which are abundantly scattered. However, the incompetent new comers may only taste the remnants of the economic cake. That is the most rational choice for the incompetent. According to Max Weber, this phenomenon shows an instrumental social action. It means that the measurement ofprofi and loss has been the most important part of their actions. Indeed, most of the new comers do not have special competence. They only depend on their physical strength in order to survive. In Karl Marx’s terminology, an individual who does not possess an ability to control the production factors (for example: natural resources, human resources, capital) will only depend on their body (physical strength) in order to survive. Therefore the informal sectors become the most rational choice. Hence street vendors, construction workers, parking attendants and other informal jobs have been the common views in the cities. This paper is trying to portray one of the informal sectors in the cities namely street vendors. Their survival strategy in the competitive city life is a point of view which is being explained and focused in this paper.